Reflux esophagitis triggered after Helicobacter pylori eradication: a noteworthy demerit of eradication therapy among the Japanese? - Iijima, Katsunori; Koike, Tomoyuki; Shimosegawa, Tooru (Frontiers in Microbiology, 2015)
In the February 2013 Revision of Insured Medical Treatment, bacterial eradication for all Helicobacter pylori-positive individuals in Japan was covered under the insurance scheme. However, reflux esophagitis is believed to occur in approximately 10% of Japanese patients who undergo eradication therapy. Hence, the risk of reflux esophagitis among such cases should be carefully considered, particularly in the treatment for H. pylori-positive patients who are otherwise healthy. The eradication of Helicobacter pylori in cases of H. pylori-positive gastritis markedly suppresses gastric inflammation, and inhibits gastric mucosal atrophy and its progression to intestinal metaplasia. In a long-term follow-up study (10-20 years), eradication treatment was found to reduce the risk of subsequent gastric cancer. However, the fact that eradication-induced reflux esophagitis could increase the long-term risk of Barrett’s esophagus and esophageal adenocarcinoma should also be considered in the Japanese population. Appropriate treatment with proton pump inhibitors should be taken into consideration for patients undergoing eradication therapy in clinical practice.